2021
DOI: 10.1177/00469580211062451
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Comparisons of Cognitive and Physical Health in Older Adults Across China, Japan, and Korea: A Systematic Review

Abstract: Background Cross-national studies are an emerging research area in public health. Specifically, cross-national health comparisons are important for understanding the factors driving the success or failure of public health policies. Therefore, this study systematically analyzed studies that compared health status (physical health and cognition) of the older adults using national panel data for three East Asian countries—China, Japan, and Korea. Methods Google Scholar and PubMed were used for the literature sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Our previous studies summarized seven studies that compared health in three countries using data from China, Korea, and Japan [ 24 ], and firstly revealed that a study on cognitive function after retirement in three countries showed that all three countries had a declining cognitive function after retirement according to sex, educational attachment, and wealth level. In this study, word recall was used to measure cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies summarized seven studies that compared health in three countries using data from China, Korea, and Japan [ 24 ], and firstly revealed that a study on cognitive function after retirement in three countries showed that all three countries had a declining cognitive function after retirement according to sex, educational attachment, and wealth level. In this study, word recall was used to measure cognitive function.…”
Section: Introductionmentioning
confidence: 99%